Response of Winter Wheat Grain Yield and Phosphorus Uptake to Foliar Phosphite Fertilization - Muaid S. Ali; Apurba Sutradhar; Ma Lourdes Edano; Jeffrey T. Edwards; Kefyalew Girma (International Journal of Agronomy)
One of the major problems that potentially hinders the use of foliar fertilization as a tool to improve nutrient use efficiency is the lack of effective formulations. A phosphite based product, Nutri-phite (3% N, 8.7% P, and 5.8% K) was used as model phosphite formulation for foliar application in winter wheat (Triticum aestivum L). Five field trials were established in the fall of 2009 and 2010 at Perkins, Perry, and Morrison, OK. Treatments encompassed the application of nitrogen (N) at 100 or 75% of crop need and phosphorus at 100 (P 100%) and 80% (P 80%) sufficiency with and without Nutri-phite. Nutri-phite was applied at one and/or two stages of wheat; GS 13 to 14 and GS 49 to 53 at the rate of 433 and 148 g ha−1 P and N, respectively. Grain yield was increased by Nutri-phite treatments, especially at Morrison. Grain P concentration of plots treated with two applications of Nutri-phite ranged from 13 to 55% more than the nontreated and standard NP received plots at Perkins in 2009/10 and Perry in 2010/11. Grain P uptake was increased due to application of Nutri-phite at Perkins in 2009/10 and Morrison and Perry in 2010/11. Combined over three year-locations, Nutri-phite increased grain P concentration by 11.6%. The higher grain P concentration of plots treated with Nutri-phite compared to the other treatments clearly demonstrates its potential in improving P status of wheat grain.